(untitled) (Pedagogy of Higher and Secondary Education, 2012)
Efimenko S. The structure and content, creativity іntelektualno teacher technology. The article offers the generalized structure of intellectually-creative potential of teacher of technologies. An author characterizes the structural components of this personality formation.